Liver Failure with Marked Hyperferritinemia: ‘Ironing Out’ the Diagnosis - Susan E Natsheh; Eve A Roberts; Bo Ngan; Peter Chait; Vicky Lee Ng (Canadian Journal of Gastroenterology)
Hemophagocytic lymphohistiocytosis (HLH) may manifest as neonatal liver failure characterized by hepatosplenomegaly, profound coagulopathy, ascites and hyperbilirubinemia. Marked hyperferritinemia may be present in these patients, mimicking perinatal hemochromatosis. Tissue specimens are critical in distinguishing these two diseases and in directing management. Clinical recognition and diagnosis of HLH can be difficult but are crucial for appropriate therapy and genetic counselling. Liver transplantation is absolutely contraindicated for patients with HLH but may be the only life-saving treatment modality for patients with perinatal hemochromatosis.